The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1063/1.1330209
|View full text |Cite
|
Sign up to set email alerts
|

The ab initio model potential method: Lanthanide and actinide elements

Abstract: In this paper we present relativistic core ab initio model potentials based on atomic Cowan-Griffin calculations, together with Wood-Boring spin-orbit operators and optimized Gaussian valence basis sets, for the lanthanide elements Ce to Lu and for the actinide elements Th to Lr. This completes the chemically relevant part of the Periodic Table. A ͓Kr,4d͔ core was chosen for Ce-Lu and a ͓Xe,4f ,5d͔ core was chosen for Th-Lr. Minimal (14s10p9d8 f )/͓2s1 p1d1 f ͔ and (14s10p11d9 f )/͓2s1 p1d1 f ͔ valence basis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
106
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(111 citation statements)
references
References 31 publications
(41 reference statements)
5
106
0
Order By: Relevance
“…These large rates imply an additional spin relaxation mechanism other than spin exchange, dipolar relaxation, and second-order spin-orbit coupling, which are well known from studies with alkali metal atoms. The electrostatic quadrupole-quadrupole interaction is a long-range mechanism for driving inelastic processes in L = 0 atoms, such as seen in metastable alkaline earth metal systems [11], however, the anisotropic charge distribution in submerged-shell atoms is confined tightly near the nucleus [12]. Thus while the quadrupole-quadrupole interaction is not expected to be shielded, the interaction strength should be far weaker than in outer-shell systems.…”
mentioning
confidence: 99%
“…These large rates imply an additional spin relaxation mechanism other than spin exchange, dipolar relaxation, and second-order spin-orbit coupling, which are well known from studies with alkali metal atoms. The electrostatic quadrupole-quadrupole interaction is a long-range mechanism for driving inelastic processes in L = 0 atoms, such as seen in metastable alkaline earth metal systems [11], however, the anisotropic charge distribution in submerged-shell atoms is confined tightly near the nucleus [12]. Thus while the quadrupole-quadrupole interaction is not expected to be shielded, the interaction strength should be far weaker than in outer-shell systems.…”
mentioning
confidence: 99%
“…27 For Pa, we observed that whereas the 5 f orbitals of neutral Pa 5 f 3 6d 1 7s 1 Ϫ 6 L obtained in Ref. 18 sis set with respect to that in Ref. 18.…”
Section: A Embedding Potentialmentioning
confidence: 57%
“…26 B. The "PaCl 6 … 2À defect cluster Relativistic Cowan-Griffin-Wood-Boring 16,17 -based core AIMPs were used for both Pa ͓͑Xe, 4 f , 5d͔ core͒ 18 and Cl ͓͑Ne͔ core͒. 27 For Pa, we observed that whereas the 5 f orbitals of neutral Pa 5 f 3 6d 1 7s 1 Ϫ 6 L obtained in Ref.…”
Section: A Embedding Potentialmentioning
confidence: 81%
See 2 more Smart Citations